Estimation of atomic charges in boron nitrides - Chkhartishvili, Levan; Dekanosidze, Shorena; Maisuradze, Nodar; Beridze, Manana; Esiava, Ramaz (Eastern-European Journal of Enterprise Technologies, 2015)
Boron nitrides (BN) are compounds with bonds of covalent–ionic type. Therefore, binding polarity is an important characteristic affecting their physical properties. Dependencies of measurable parameters on static effective charges of constituent atoms are so complex that, these are virtually undetectable experimentally. As for the theoretically obtained atomic charges in boron nitrides, they are characterized by a significant scatter making them almost unreliable. The general reason for this lies in the impossibility of unambiguous division of the electron density between atoms of elements. It pushes the search for a semiempirical solution of the problem. We have derived the expression for the effective charge number in a binary compound (effective charges of B and N atoms should be and , respectively) depending on number of molecules in primitive parallelogram, its sectional area transverse to the external electric field direction, Young’s modulus and permittivity in same direction. Semiempirically estimated values of (in - and -directions) are physically reasonable: hexagonal h-BN – 0.35 and 0.09, cubic c-BN – 0.49, and wurtzite-like w-BN boron nitrides – 0.76 and 0.50. Also quite natural are qualitative conclusions: in h-BN intra-layer bonds polarity is much stronger than that between hexagonal layers; bonds are stronger polarized in denser modifications c-BN and w-BN, which are characterized by higher coordination numbers as well; bonds polarities in c-BN and along -axis in w-BN are almost indistinguishable; and bonds polarities in - and -directions in w-BN are different. Obtained static charges can be used in the refinement of the BN electron structure calculations.